LA CRISIS TOTAL DEL GABINETE MINISTERIAL EN EL CONSTITUCIONALISMO PERUANO - Torralba López, Marco Rodrigo (Revista de Derecho, 2020)
Article 133 of the Peruvian Constitution of 1993 contains the expression called “total cabinet crisis”, a phrase whose concept and scope have not been delimited neither by lawmakers nor by constitutional authors. This indeterminacy creates inconveniences in parliamentary and government practice, thus contributing to the recent political crisis in Peru. Therefore, in the present study, through diverse backgrounds and interpretations, we will try to propose a definition and identify the legal consequences of the mentioned constitutional provision, in order to unify criteria that cooperate to a better legal understanding of the matter and, ultimately, to the political stability of the country.
Keywords: total cabinet crisis; ministerial crisis; cabinet